2022
DOI: 10.1186/s12887-022-03455-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of early skin-to-skin contact and its impact on exclusive breastfeeding during the maternity hospitalization

Abstract: Background Early essential newborn care has been implemented in countries regardless high or low neonatal mortality. This study aims to investigate the current practice of skin-to-skin contact (SSC) and its effect on exclusive breastfeeding during the hospital stay. Methods This is a cross-sectional study of 1812 Vietnamese mothers in multicenter. A questionnaire answered by the mothers was used to assess the duration of both SSC and breastfeeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
5
0
5
Order By: Relevance
“…This prevalence rate was higher than the prevalence rate in India (14.5%) 18 and Nigeria (10%) 7 but lower than Nepal (16.5%), 18 Ethiopia (24.3%) 19 and Vietnam (88.7%). 20 Other studies conducted in Bangladesh showed a much higher prevalence (28% 4 and 26% 7 ). However, the first study was limited to only 10 districts and included samples from only district level households.…”
Section: Discussionmentioning
confidence: 92%
“…This prevalence rate was higher than the prevalence rate in India (14.5%) 18 and Nigeria (10%) 7 but lower than Nepal (16.5%), 18 Ethiopia (24.3%) 19 and Vietnam (88.7%). 20 Other studies conducted in Bangladesh showed a much higher prevalence (28% 4 and 26% 7 ). However, the first study was limited to only 10 districts and included samples from only district level households.…”
Section: Discussionmentioning
confidence: 92%
“…Internacionalmente, estudo transversal, no Vietnã, com 1.812 puérperas, mostrou a importância não somente da realização da prática do CPP, mas também de os profissionais estarem atentos à sua duração, visto que a prevalência de aleitamento materno exclusivo foi maior em RNs que experimentaram o contato pele a pele por 15 a 90 minutos e por mais de 90 minutos 24 .…”
Section: Discussionunclassified
“…Particularmente la LME, es decir la práctica en la que el/la bebé recibe sólo leche materna sin ningún otro alimento o líquido hasta los 6 meses de edad, es una importante variable protectora contra la morbi-mortalidad infantil debido a infecciones respiratorias y del tracto gastrointestinal (Hossain & Mihrshahi, 2022). La LM podría salvar por encima de 800.000 vidas al año en todo el mundo, dado que la leche materna provee al lactante de los nutrientes y componentes inmunológicos precisos que necesita para un desarrollo adecuado (Giang et al, 2022). Principalmente, los primeros 1000 días, que van desde la concepción hasta los dos años de vida, son cruciales para el desarrollo del/la bebé.…”
Section: Beneficios De La Lm Y Causas De Abandono a Nivel Mundialunclassified
“…El olor de la madre y de la leche materna facilita el agarre del pezón contribuyendo así al inicio de la lactancia. Escuchar los latidos del corazón y la voz de la madre, de baja frecuencia, le proporciona a el/la bebé una mayor seguridad emocional, el contacto con el/la bebé y la succión del pecho provocan un aumento de oxitocina y de las beta-endorfinas que favorecen la contracción uterina y la eyección de calostro; además, el COPAP facilita la expulsión más temprana de la placenta, la reducción de las hemorragias, el aumento de la autoeficacia en la lactancia y la disminución de los niveles de estrés materno (Costa-Romero et al, 2019;Giang et al, 2022).…”
Section: Contacto Piel Con Pielunclassified